Achievements in impact assessment of agricultural research: IITA experience, 2001-2006 - Manyong, Victor M.; Alene, A.; Sanogo, D.; Coulibaly, O.; Abele, S.; Nkamleu, G.B. (2006)
The purpose of this document is to take stock of the achievements of and gaps in impact assessment (IA) research at IITA since the last External Program and Management Review in 2001 and to highlight elements of a strategy for the future of impact studies at the Institute. Our vision of IA is that it is a continuous process. It covers a wide range of interrelated activities including baseline studies, ex ante impact, on-farm technology evaluation, adoption studies, and ex post impact. IITA has developed a framework for conceptualizing and promoting impact culture in agricultural research to guide and facilitate the implementation of IA research. During the conduct of impact studies, both quantitative and qualitative techniques have been applied. IITA has made tremendous achievements in assessing the impact of its Research-for-Development products and has contributed significantly to capacity building, communication of findings from IA, and development of international public goods. The review concludes with major IA research initiatives and challenges ahead.